Demonstration Drawing Method and Fifth Grade Creativity Growth: Metode Gambar Demonstrasi dan Pertumbuhan Kreativitas Siswa Kelas Lima - Arahman, Ba’Agil Widya; Wati, Tri Linggo (Indonesian Journal of Education Methods Development, 2026)
General Background: Creativity is a fundamental component of human intelligence and plays an essential role in elementary education, particularly in visual arts learning where students are encouraged to express ideas through drawing activities. Specific Background: In Al-Ishlah Elementary School, many fifth-grade students experienced difficulties in expressing ideas independently and tended to produce similar and basic drawings, indicating limited creative development. Knowledge Gap: Although the demonstration method has been widely discussed in educational contexts, limited classroom action research specifically examines its application in structured shape drawing activities to foster creativity in upper elementary students. Aims: This study aimed to determine whether the application of the shape-drawing demonstration method could increase the creativity of fifth-grade students at Al-Ishlah Elementary School. Results: Using a two-cycle classroom action research model based on Kurt Lewin, the findings showed a progressive increase in students’ creativity scores from 70.08 in the initial observation to 85.49 in Cycle I and 90.75 in Cycle II, indicating measurable improvement after reflective refinement of instructional practice. Novelty: The study highlights structured shape-based demonstration as a practical classroom strategy to reduce students’ hesitation and dependence on peers during drawing tasks. Implications: The findings suggest that carefully implemented demonstration techniques can support creative expression in visual arts education and provide practical guidance for elementary school teachers in designing structured art instruction. Keywords: Demonstration Method, Creativity, Classroom Action Research, Drawing Shapes, Elementary Education Key Findings Highlights Creativity scores increased consistently across two classroom action cycles. Reflective revision of instruction reduced students’ hesitation and imitation behavior. Structured visual modeling supported independent artistic expression.